Analyzing qualitative data with computer software. - Weitzman, E A (1999)
OBJECTIVE: To provide health services researchers with an overview of the qualitative data analysis process and the role of software within it; to provide a principled approach to choosing among software packages to support qualitative data analysis; to alert researchers to the potential benefits and limitations of such software; and to provide an overview of the developments to be expected in the field in the near future. DATA SOURCES, STUDY DESIGN, METHODS: This article does not include reports of empirical research. CONCLUSIONS: Software for qualitative data analysis can benefit the researcher in terms of speed, consistency, rigor, and access to analytic methods not available by hand. Software, however, is not a replacement for methodological training.